POTENSI HUTAN SAGU RAKYAT DI SERAM BARAT, PROPINSI MALUKU - Boen M Pumama; Subandi At; Hendro Prahasto (Jurnal Penelitian Hasil Hutan, 1984)
Sago, one of  some carbohydrate sources  which  has a great potential as food  stock,  grows  naturally  and distribute through out  Indonesian  archipelago,  Maluku is one  of  several  areas having  sago forest.The study  on sago forest  at West Seram in 1979,  showed that the number of  mature  trees per hectare  was 17 trees, consisted  of  several sago species  namely  tuni,  molat and makanaru.  The sago production per  tree was 419.9  kg of  wet sago or 292,5 kg  of dried  sago.